Effect of calcium and nitrogen spraying on growth, yield and BER disorder of watermelon “Top yield” var.(Citrullus lanatus) in Sulaimani Governorate - Omar, Samal Jalal; Mahmood, Ayub Karim (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was carried out at Kanipanka Research Station / Sulaymani during growing season of (2015) to study the effect of nitrogen and calcium spraying and their interaction on growth, yield and Blossom-end rot% incidence of watermelon plant (“Top yield” var.).This study included spraying nitrogen as three concentrations (0, 200 and 400 mg N l-1) using urea fertilizer and spraying calcium as four concentrations (0, 100, 300, 600 mg Ca l-1) concentrations using CaCl2. The study's characters were reproductive growth, yield and Blossom-end rot percentage (BER %). The results showed that maximum infected fruits % (32.26 %) was obtained from Ca0. While Ca3 (600 mg l-1) gave minimum BER infected fruit (6.64 %) and maximum number of flower.plant-1 (10.1), yield plant-1 (4.98 kg), fruit weight (3.86 kg) and total yield (53.17 t ha-1).N2 (400mg l-1) gave highest yield plant-1 (4.60 kg) and total yield.ha-1 (48.11t). Nitrogen and Calcium combination (400mg l-1 N x 600mg l-1Ca) gave the highest number of flower plant-1 (10.30) and minimum BER% (4.42%). (200mg l-1 N x control Ca) gave the highest yield plant-1 (5.36kg) and total yield ha-1 (55.06t), while (200mg l-1 N x 600mg l-1Ca) and (N0 x 600 mg l-1Ca) gave the highest number of fruits plant-1 (1.41) and fruit weight (4.02kg), respectively.
Keywords: Watermelon Calcium; Nitrogen BER growth yield